The Influence Of Teaching Readiness, Perception Of The Teaching Profession, And Family Environment On Interest In Becoming A Teacher - Dayka, R. Dewa Wahyu Happy; Winatha, I Komang; Suroto, Suroto; Rusman, Tedi; Rizal, Yon; Nurdin, Nurdin (Economic Education and Entrepreneurship Journal, 2023)
Economic Education FKIP University of Lampung is one of the study programs that produce prospective teacher graduates. Becoming a teacher requires an interest in students. Therefore, this study aims to determine the influence of teaching readiness, perception of the teaching profession, and family environment on interest in becoming a teacher in Economic Education students of the University of Lampung. The method used in this study is a survey method with a quantitative approach. The population in this study was 235 students, with a simple random sampling technique of 148 students. Data were tested using partial and simultaneous analysis. The results of the hypothesis show that there is a partial and simultaneous influence on teaching readiness, perception of the teaching profession, and family environment on interest in becoming a teacher of Economic Education students at the University of Lampung. Teacher education programs should prioritize the development of effective teaching skills and knowledge, so they need to be supported by improving image, family environment, and policymakers.Keywords: Family environment, Interest in becoming a teacher, Perception of the teaching profession, Readiness to teachDOI: http://dx.doi.org/10.23960/E3J/v6i1.89-96